A health-conformant reading of the GDPR’s right not to be subject to automated decision-making - van Kolfschooten, Hannah B (Medical law review, 2024)
Abstract As the use of Artificial Intelligence (AI) technologies in healthcare is expanding, patients in the European Union (EU) are increasingly subjected to automated medical decision-making. This development poses challenges to the protection of patients’ rights. A specific patients’ right not to be subject to automated medical decision-making is not considered part of the traditional portfolio of patients’ rights. The EU AI Act also does not contain such a right. The General Data Protection Regulation (GDPR) does, however, provide for the right ‘not to be subject to a decision based solely on automated processing’ in Article 22. At the same time, this provision has been severely critiqued in legal scholarship because of its lack of practical effectiveness. However, in December 2023, the Court of Justice of the EU first provided an interpretation of this right in C-634/21 (SCHUFA)—although in the context of credit scoring. Against this background, this article provides a critical analysis of the application of Article 22 GDPR to the medical context. The objective is to evaluate whether Article 22 GDPR may provide patients with the right to refuse automated medical decision-making. It proposes a health-conformant reading to strengthen patients’ rights in the EU.